The Formation of Nanoparticles between Small Interfering RNA and Amphipathic Cell-Penetrating Peptides - Ly Pärnaste; Piret Arukuusk; Kent Langel; Tanel Tenson; Ülo Langel (Elsevier, 2017)
Cell-penetrating peptides (CPPs) are delivery vectors widely used to aid the transport of biologically active cargoes to intracellular targets. These cargoes include small interfering RNAs (siRNA) that are not naturally internalized by cells. Elucidating the complexities behind the formation of CPP and cargo complexes is crucial for understanding the processes related to their delivery. In this study, we used modified analogs of the CPP transportan10 and investigated the binding properties of these CPPs to siRNA, the formation parameters of the CPP/siRNA complexes, and their stabiliy to enzymatic degradation. We conclude that the pH dependent change of the net charge of the CPP may very well be the key factor leading to the high delivery efficiency and the optimal binding strength between CPPs to siRNAs, while the hydrophobicity, secondary structure of the CPP, and the positions of the positive charges are responsible for the stability of the CPP/siRNA particles. Also, CPPs with distinct hydrophobic and hydrophilic regions may assemble into nanoparticles that could be described as core-shell formulations.